The Wiley handbook of early childhood development programs, practices, and policies - Votruba-Drzal, Elizabeth; Dearing, Eric (Hoboken, New Jersey John Wiley & Sons, Inc., 2017)
"This unique and important bookprovides a comprehensive overview of the current theory, practices, and policies in early childhood development withinthe contexts of family, school, and community, and society at large. Moreover, it synthesizes scientifically rigorous research from an array of disciplines in an effort to identify the most effective strategies for promoting early childhood development"--Provided by publisher.
Part I: The state of young children in the United States -- Chapter 1. The state of young Children in the United States: school readiness / Terri J. Sabol and Robert C. Pianta -- Chapter 2. The state of young children in the United States: A developmental Psychopathology perspective on the mental health of preschool children / Susan B. Campbell -- Chapter 3. Early childhood health disparities, biological embedding, and life? course health / Daniel Berry -- Chapter 4. Social and contextual risks / Robert H. Bradley -- Part II: Theoretical and Empirical Contexts of Applied Developmental Science of Early Childhood -- Chapter 5: From the lab to the contexts in which children live and grow: historical perspectives on the field / Pamela A. Morris and Maia C. Connors -- Chapter 6. What does it mean to be evidence? based? / Margaret R. Burchinal and Nina E. Forestieri -- Chapter 7. Neural development in context: differences in neural structure and function associated with adverse childhood experiences / Emily C. Merz and Kimberly G. Noble -- Part III: early childhood education and care -- Chapter 8. Publicly supported early care and education programs / W. Steven Barnett, Elizabeth Votruba? Drzal, Eric Dearing, and Megan E. Carolan -- Chapter 9. Early childhood education and care for dual language learners / Lianna Pizzo and Mariela Páez -- Chapter 10. Early childhood education and care for children with disabilities / Penny Hauser? Cram, Miriam Heyman, and Kristen Bottema? Beutel -- Chapter 11. classroom? based early childhood Interventions / Stephanie Jones, Dana Charles McCoy and Lauren Hay -- Chapter 12. Child Care and Child Development in the United States: Where Have We Come From, what do we Know now, and where are we going? / Anna D. Johnson -- Part IV: Parenting, family, and dual? generation programs -- Chapter 13. Family? School Partnerships in Early Childhood / Susan M. Sheridan, Amanda L. Moen, and Lisa L. Knoche -- Chapter 14. Parenting and Home visiting interventions / Nancy Donelan? McCall -- Chapter 15 The Two? generation approach to building human capital: Past, Present, and Future / Margo Gardner, Jeanne Brooks? Gunn, and P. Lindsay Chase? Lansdale -- Part V: Public Policy and Young Children -- 16 Immigration policy and early childhood development / Soojin Oh Park and Hirokazu Yoshikawa -- 17 Marriage policy and early childhood development / Rebekah Levine Coley -- Chapter 18. Child welfare policy / Kristen S. Slack and June Paul -- Chapter 19. Effects of United States income and work supports policies on children in low? income families / Aletha C. Huston -- Chapter 20. The role of conditional cash transfer programs in promoting early childhood development in the United States / Sharon Wolf, Juliette Berg, Pamela A. Morris, and J. Lawrence Aber -- Chapter 21. Work? Family Policies / Anna Gassman? Pines and Rachel Goldstein.
Includes bibliographical references and index.
Keywords: Early childhood education